2002
DOI: 10.1038/sj.bjp.0704517
|View full text |Cite
|
Sign up to set email alerts
|

Aconitine facilitates spontaneous transmitter release at rat ventromedial hypothalamic neurons

Abstract: 1 The eects of aconitine, an Aconitum alkaloid, on spontaneous inhibitory and excitatory postsynaptic currents (IPSCs and EPSCs respectively) were investigated in the mechanically dissociated rat ventromedial hypothalamic (VMH) neurons in which native presynaptic nerve terminals remained intact. 2 Under current-clamp conditions, aconitine (3610 76 M) depolarized the neuron with generating the action potentials. The aconitine-induced depolarization was markedly suppressed in the presence of CNQX but it was faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…After 20 min, isolated neurons that adhered to the bottom of the dish were used for electrophysiological recordings. These mechanically dissociated neurons often preserved some functional nerve terminals, including those that release glutamate (Yamanaka et al , 2002; Akaike and Moorhouse, 2003; Ye et al , 2004; Zhu and Lovinger, 2005; Jang et al , 2006). …”
Section: Methodsmentioning
confidence: 99%
“…After 20 min, isolated neurons that adhered to the bottom of the dish were used for electrophysiological recordings. These mechanically dissociated neurons often preserved some functional nerve terminals, including those that release glutamate (Yamanaka et al , 2002; Akaike and Moorhouse, 2003; Ye et al , 2004; Zhu and Lovinger, 2005; Jang et al , 2006). …”
Section: Methodsmentioning
confidence: 99%
“…1 to figure out its three-dimensional shape in space for the researchers. The imagination of its spatial shape of the molecule will clearly help the researchers in understanding the toxic interaction of aconitines with tetrodotoxinsensitive Na + channel (Yamanaka et al, 2002). There are two intermolecular hydrogen bonds which stabilize the molecular packing of tuguaconitine in the crystal.…”
Section: Resultsmentioning
confidence: 98%
“…al., , 1986. Aconitum alkaloids are potent neurotoxin known to activate voltage-dependent Na + channels, and there are trials to understand the molecular mode of action for the physiological effects of the compounds (Lao et al, 1990;Almanza et al, 1997;Yamanaka et al, 2002). However, it is very hard to imagine the overall shape of the molecule from the ordinary 2D-diagram (Fig.…”
Section: Introductionmentioning
confidence: 97%
“…[ 46 ] Specialized neurophysiological research, based on patch-clamp techniques mainly related to the neuron excitability process, has demonstrated that a low physiological Acn dose (10 −6 M) affects individual pre-synaptic rat neuron excitability by opening Na+ channels. [ 47 ]…”
Section: Discussionmentioning
confidence: 99%